COVID-19 and Level of Public Trust Towards Jokowi’s Good Governance (Universitas Padjadjaran, 2022)
This article examines COVID-19 and the level of trust of the Indonesian people in the good governance of the Jokowi’s administration related to the government’s slow response at the start of this pandemic. Differences in statements from several government officials regarding the existence of COVID-19 had caused the level of public trust in Jokowi’s administration to decline. Jokowi’s programs covering maritime, infrastructure, bureaucracy, cooperation, were delayed due to COVID-19. This will be a problem for Indonesia if it is not supported by public trust. The author will analyze based on the concept of good governance and how the level of Indonesian public trust in the good governance of the Jokowi administration during COVID-19. The used research method is qualitative with secondary data sources from various literature regarding the good governance of Jokowi’s administration. This study also uses tracking media, which data is taken from the news websites and social media regarding the Indonesian public’s response to the good governance of Jokowi’s administration during the pandemic. From media tracking, the results can be seen how the level of public trust in Jokowi’s good governance before and after COVID-19.